ANALISIS PENILAIAN PEMBELAJARAN DI TK SE-KECAMATAN BELITANG OKU TIMUR - Kurnia Mustika Weni; Hasmalena hasmalena; syafdaningsih syafar (FKIP Universitas sriwijaya, 2017)
This research which is goals is to determine the presentage of the assessment of the lessons conducted by teachers kindergarten by using quantitative descriptive method. Sampling technique in this research there are two that is area probability sampling taking representatives from every region within the population and purposive sampling taking into account that the results of accreditation of kindergarten (A, B, C or not yet accredited), distance of research place and fund owned by researcher. Samples amounted to 6 institutions kindergarten in Belitang District OKU East. Data collection uses observation sheets and documentation displayed in the form of values consisting of 5 indicators. The result of the research indicates that 1 kindergarten institution or 17% kindergarten institute do a very good learning appraisal, 4 kindergarten institute or 66% kindergarten institute do learning well studying, and 1 kindergarten institution or 17% kindergarten institute do poorly assessment of learning. The mean score of observation sheets obtained from the results of the research assessment in the kindergarten in Belitang OKU Timur subdistrict was 68 with good category. Assessment of lessons learned by Belitang District Kindergarten teachers has followed the learning assessment procedure but in the learning assessment has not included parental involvement.